ANALYSIS OF FACTORS AFFECTING EXCLUSIVE BREASTFEEDING IN INFANTS AGED 6-30 MONTHS AT KAGUNGAN CLINIC - Muthia, Hany Adeliana; Rahmadhena, Melisa Putri (HEARTY, 2025)
Background: Exclusive breastfeeding is the practice of giving only breast milk to babies until they reach 6 months of age, without adding additional fluids or food. The prevalence of exclusive breastfeeding in infants aged 0-1 months reached 48.7%, but decreased to 42.2% at the age of 2-3 months, months reached 48.7%, but decreased to 42.2% at the age of 2-3 months, and continued to decrease with increasing age, namely 36.6% at the age of 4-5 months and 30.2% at the age of 6 months. Objective: To analyze the factors of exclusive breastfeeding in infants aged 6-30 months at Kagungan Clinic. Methods: The research conducted was quantitative research using an analytic design. This study used a cross sectional method. Total sample needed for this research is 60 people.Results: Of the 60 respondents, there were 32 (53.3%) respondents with good knowledge about exclusive breastfeeding, 22 (36.6) of them who provided exclusive breastfeeding and 10 (16.7%) others who did not provide exclusive breastfeeding did not know about exclusive breastfeeding. Conclusions and Suggestions: The conclusion of this study is that maternal age can have an influence on exclusive breastfeeding for various reasons related to health and social factors. Nevertheless, it is important to remember that these factors are general and do not always apply to every situation or individual.